Inflammatory response to cold injury in remote organs is reduced by corticotropin-releasing factor - (:unkn) unknown (ELSEVIER SCIENCE BV, 2001)
Current experimental evidence concerning the potential activity of corticotropin releasing factor (CRF) in inflammatory processes still remains controversial. To determine whether CRF has protective effects: on three remote organs (liver, lung and stomach) affected by cold injury and to characterize the role of neutrophils in cold-induced inflammation, dorsums of anesthetized rats were exposed for 5 min to a 22% NaCl solution maintained at -20 +/- 0.5 degreesC and the rats were sacrificed at 24 h after the cold injury. The results indicate that cold-exposure-induced edema in the liver, lung and stomach was: blocked by subcutaneous: (s.e.; 1.2 and 12 nmol/kg; 30 min before cold trauma) CRF pretreatment, while the central administration of CRF (intracisternally (i.e.); 0.30 and 1.5 nmol/rat; 15 min before cold) had the similar effect at the higher dose. Histological assessment and the tissue myeloperoxidase activities: also revealed that CRF given peripherally has: a protective role in damage generation. Moreover, CRF had a facilitatory effect in the recovery of the body temperature following cold exposure. In conclusion, CRF is likely to act on its peripheral receptors in the inflamed remote organs, suppressing the edematogenic effects of inflammatory mediators, some of which are neutrophil-derived. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: MPO; edema; inflammation; neutrophils; HORMONE GENE-EXPRESSION; RAT PAWSKIN; INFLAMED TISSUE; THERMAL-INJURY; INTERLEUKIN-1; TRANSCRIPTION; HYPOTHALAMUS; RECEPTORS; SYSTEM; ASSAY